Assessing muscular power in older adults: evaluating the predictive capacity of the 30-second chair rise test - Mahato, Niladri Kumar; Davis, Alexandria; Simon, Janet E.; Clark, Brian C. (Frontiers in Aging, 2024)
Background: Timed chair rise tests are frequently used as a substitute for assessing leg muscle strength or power. To determine if timed chair rise tests are an indicator of lower extremity muscle power, we examined the relationship between the repetitions completed in a 30-second chair rise test and the power generated during the test. Methods: Seventy-five individuals participated in this study (n=30<65 years and 4565 years). Participants underwent a 30-second chair rise test while instrumented with a power analyzer. Handgrip strength was also evaluated.The relationship between chair rise repetitions and average chair rise power was R 2 =0.32 (p<0.001). Chair rise repetitions when regressed on a total (i.e., summed) chair rise power, it yielded R 2 =0.70 with data from all participants combined (p<0.001). A mediation analysis indicated that anthropometrics partially mediates the relationship between chair rise repetitions and total chair rise power accounting for 2.8 to 6.9% of the variance. Conclusions:Our findings indicate that in older adults, the overall performance of chair rises offers limited information about the average power per rise but is more indicative of the cumulative power exerted. Thus, the total number of chair rises in a 30-second test is likely a more comprehensive metric of overall muscular power, reflecting endurance aspects as well. Additionally, we found that personal physical attributes, such as height and weight, partially influence the link between chair rise count and total power, highlighting the importance of factoring in individual body metrics in assessments of muscular performance.